ANALISIS PERTIMBANGAN HUKUM HAKIM TERHADAP PUTUSAN SENGKETA MEREK (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 650K /PDT.SUS-HKI/2021) - NIM. A1011201273, FERDINAND DELFORT SIRAIT (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractLaw Number 20 of 2016 on Trademarks serves as the legal basis for settling trademark disputes in Indonesia, providing exclusive rights to trademark owners. The trademark dispute